Hippocampal Memory Recovery After Acute Stress: A Behavioral, Morphological and Molecular Study - Aguayo, Felipe Ignacio; Tejos-Bravo, Macarena; Díaz-Véliz, Gabriela; Pacheco, Aníbal; García-Rojo, Gonzalo; Corrales, Wladimir; Olave, Felipe Antonio; Aliaga, Esteban; Ulloa, José L.; Avalos, Ana M.; Román-Albasini, Luciano; Rojas, Paulina S.; et al. (Frontiers in Molecular Neuroscience, 2018)
Several studies have shown that a single exposure to stress may improve or impair learning and memory processes, depending on the timing in which the stress event occurs with relation to the acquisition phase. However, to date there is no information about the molecular changes that occur at the synapse during the stress-induced memory modification and after a recovery period. In particular, there are no studies that have evaluated—at the same time—the temporality of stress and stress recovery period in hippocampal short-term memory and the effects on dendritic spine morphology, along with variations in N-methyl-D-aspartate (NMDA) and α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunits. The aim of our study was to take a multidimensional approach to investigate concomitant behavioral, morphological and molecular changes induced by a single restraint stress exposure (2.5 h) and a recovery period of 6 and 24 h in rats. We found that acute stress elicited a reduced preference to explore an object placed in a novel position (a hippocampal-dependent task). These changes were accompanied by increased activity of LIM kinase I (LIMK; an actin-remodeling protein) and increased levels of NR2A subunits of NMDA receptors. After 6 h of recovery from stress, rats showed similar preference to explore an object placed in a novel or familiar position, but density of immature spines increased in secondary CA1 apical dendrites, along with a transient rise in GluA2 AMPA receptor subunits. After 24 h of recovery from stress, the animals showed a preference to explore an object placed in a novel position, which was accompanied by a normalization of NMDA and AMPA receptor subunits to control values. Our data suggest that acute stress produces reversible molecular and behavioral changes 24 h after stress, allowing a full reestablishment of hippocampal-related memory. Further studies need to be conducted to deepen our understanding of these changes and their reciprocal interactions.Adaptive stress responses are a promising avenue to develop interventions aiming at restoring hippocampal function impaired by repetitive stress exposure.